2017
DOI: 10.3389/fmicb.2017.01626
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Zinc Homeostasis in Acanthamoeba castellanii as a Possible Antifungal Strategy against Cryptococcus gattii

Abstract: Cryptococcus gattii is a basidiomycetous yeast that can be found in the environment and is one of the agents of cryptococcosis, a life-threatening disease. During its life cycle, cryptococcal cells take hold inside environmental predators such as amoebae. Despite their evolutionary distance, macrophages and amoebae share conserved similar steps of phagocytosis and microbial killing. To evaluate whether amoebae also share other antifungal strategies developed by macrophages, we investigated nutritional immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 62 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…It is known that continued sub culturing affects phenotypic and genotypic characteristics of cryptococcal cells ( Cavalcante et al, 2007 ). However, the assessment of virulence profiles of the R265 strain by our group over the last decade did not revealed major differences ( Schneider et al, 2012 ; Godinho et al, 2014 ; Feder et al, 2015 ; Schneider Rde et al, 2015 ; Joffe et al, 2017 ; Ribeiro et al, 2017 ). In this way, the differences of virulence properties between CG strains and R265 could not be caused by sub culturing and should be considered due to inherent genotypic and phenotypic characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…It is known that continued sub culturing affects phenotypic and genotypic characteristics of cryptococcal cells ( Cavalcante et al, 2007 ). However, the assessment of virulence profiles of the R265 strain by our group over the last decade did not revealed major differences ( Schneider et al, 2012 ; Godinho et al, 2014 ; Feder et al, 2015 ; Schneider Rde et al, 2015 ; Joffe et al, 2017 ; Ribeiro et al, 2017 ). In this way, the differences of virulence properties between CG strains and R265 could not be caused by sub culturing and should be considered due to inherent genotypic and phenotypic characteristics.…”
Section: Discussionmentioning
confidence: 87%
“…Brazilian C. gattii VGII population was found with the highest diversity in the world, and the link between C. gattii VGII population in Brazil and other parts of the world indicates that Brazil is the origin of this subtype of C. gattii that spreads worldwide (Souto et al ., ). The survival of Cryptococcus cells within environmental amoebae had been demonstrated similar to the survival of Cryptococcus cells in macrophages, and some mechanisms, such as zinc homeostasis and polysaccharide accumulation, had been revealed related to the survival of intracellular Cryptococcus cells (Steenbergen et al ., ; Ribeiro et al ., ). It had also been shown that Cryptococcus could grow and reproduce on media with plant material or dead plant materials, which indicates that plants could be the ecological niche of this species (Springer et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Some of these reports highlight that fungi-FLA interactions in the environment mimic those found between fungi and host cells, possibly contributing to the development of virulence and immune escape strategies. (187,188,189) One study identified Pseudomonas in Acanthamoeba isolates. (86) Another survey adopted a co-culture model between this FLA genus and methicillin-resistant Staphylococcus aureus, showing mutual effects on cell growth or differentiation.…”
Section: Clinical References and The Risks Of Fla Infectionsmentioning
confidence: 99%